1996
DOI: 10.1177/002199839603000107
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Properties of IM7/PETI Composites

Abstract: A phenylethynyl terminated imide (PETI) oligomer from the reaction of 3,3',4,4'-biphenyltetracarboxylic dianhydride, an 85:15 molar ratio of 3,4'-oxydianiline and 1,3-bis(3-aminophenoxy)benzene and 4-phenylethynylphthalic anhydride as the end-capper at a theoretical number average molecular weight (Mn) of - 5,000 g/mol was evaluated as a composite resin matrix. Unidirectional prepreg was made by coating an N-methylpyrrolidinone solution of the amide acid oligomer onto unsized IM7. The thermal and Theological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 7 publications
0
70
0
Order By: Relevance
“…During the HSR, a molding cycle that includes 250°C/1 hr B-stage and 371°C/1 hr with 200 psi consolidation was successfully designed for the IM7/PETAA-5/NMP prepreg system. Void-free laminates with sizes up to 12" x 12" and 24 plies were fabricated with very good mechanical properties reported [7]. For these small parts, the imidization and (minimal, if any) crosslinking reactions occurring in the PETAA-5/NMP matrix during the 250°C/1 hr B-staging period did not compromise matrix resin processability to an unacceptable level.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…During the HSR, a molding cycle that includes 250°C/1 hr B-stage and 371°C/1 hr with 200 psi consolidation was successfully designed for the IM7/PETAA-5/NMP prepreg system. Void-free laminates with sizes up to 12" x 12" and 24 plies were fabricated with very good mechanical properties reported [7]. For these small parts, the imidization and (minimal, if any) crosslinking reactions occurring in the PETAA-5/NMP matrix during the 250°C/1 hr B-staging period did not compromise matrix resin processability to an unacceptable level.…”
Section: Introductionmentioning
confidence: 88%
“…PETAA-5/NMP resin was taken from wet prepreg flash and thermally pre-treated at 250°C/1 hr in an oven before measurement. An earlier study reported that less than 0.5% w/w volatiles remained after the 250°C/1 hr thermal pre-treatment [7]. Because of the presence of reinforcing fibers, prepreg viscosities (in Figure 1b)) were artificially inflated about two orders of magnitude when compared to the neat resin viscosity.…”
Section: Mechanical Measurementsmentioning
confidence: 95%
See 2 more Smart Citations
“…The extent of imidization can be determined from the heights of the absorption bands for imides I and III, terminated imide oligomers for high-temperature aerospace and aircraft applications, known as phenylethynyl-terminated imide (LaRC PETI), were developed at the National Aeronautics and Space Administration (NASA) Langley Research Center, USA [13][14][15][16][17][18][19]. These materials have broader processing windows and thermal oxidative stability than simple ethynyl-terminated materials, and consequently have many practical advantages as a potential material for coatings, adhesives, films, and composite matrix resins [20,21].…”
Section: Phenylethynyl-terminated Imide Polymermentioning
confidence: 99%